On Stationary $p(·)$-Kirchhoff-Type Problem with Mixed Boundary Conditions (Analysis in Theory and Applications, 2025)
In this paper, we consider the stationary Kirchhoff-type equation with mixedboundary conditions in a variable exponent Sobolev space. We show the existence ofa weak solution. Moreover, we prove the existence of a non-trivial weak solution andinfinitely many weak solutions under some hypotheses by variational methods.